Psychological intervention programs for children with overweight and obesity: Systematic review - Straffon Olivares, Diana Karina; Bautista-Díaz, María Leticia (Mexican Journal of Medical Research ICSA, 2021)
Currently obesity is a public health problem that is characterized by being a chronic disease, caused by various factors ranging from genetic, metabolic or sociocultural problems. Objective: To analyze psychological interventions for overweight and obesity, in children, with favorable results in the participants. Method: A systematic review was carried out on the internet based on articles published in Crossref and PubMed by using keywords such as “interventions for overweight children”, “Children obesity interventions”, “psychological interventions in children”. Results: In a first revision, 79 psychological programs applied in children were found, when reviewing the programs, it was found that only 19 had favourable results in the participants. Conclusion: The interventions had positive results; however, it will be necessary to design more adequate interventions for obese and overweight people, and contribute more to the solution of these public health problems.